The Effectiveness of Synchronous and Asynchronous Participatory Activities Via Facebook in the Achievement of the Second Grade Secondary Students in Computer Curriculum - Alqarni, Ahmed Mohsen; Zidane, Ashraf Ahmed (Journal of Curriculum and Teaching Methodology, 2022)
This research aimed to identify The Effectiveness of Synchronous and Asynchronous Participatory Activities Via Facebook in the achievement of the second grade Secondary Students in Computer Curriculum. The researcher used the experimental method, with a sample of (24) students from the second grade Secondary at Ibn Abd Albar Secondary school in Makkah Region, The sample was divided into two experimental equal groups. Each group was consisted of 12 students. the first group participated in synchronous activities via Facebook network. the second group participates in asynchronous activities via Facebook network. The research tool (achievement test), prepared by the researcher, was applied on the groups. The current research shows that there are statistically significant differences at the level (0.05) between the averages of ranks of the experimental groups in the achievement test for the favor of the second experimental group. The researcher recommends the need to take advantage of the social networking capacity in the practice of learning activities, and to benefit from the results of the current study and related electronic activities on the practical level in educational institutions, In light of the findings of the present study it is preferred to use the pattern of asynchronous electronic activities, The researcher also proposes for future studies on other educational curricula at different stages, with other dependent variables that were not measured in the current study.